Moderated effect of teachers’ attitudes to the contribution of technology competencies on TPACK - Hendra Yulisman; Ari Widodo; R. Riandi; Cut Intan Evtia Nurina (University of Muhammadiyah Malang, 2019)
Technological Pedagogical and Content Knowledge (TPACK) can be seen as teacher’s skills and abilities in choosing and using technology effectively. However, information about the teacher’s attitudes contribution to technology competencies and science teacher's TPACK is still limited. Therefore, this study aimed to analyze the relationship between teacher's technology competencies and their TPACK as well as the effect of teacher’s attitudes as a moderating effect on relation between these two variables. This survey research used total sampling technique which involved 88 science teachers from junior high school of Kota Banda Aceh. The instruments consisted of questionnaires and multiple-choice test which were distributed directly to the teachers. The data analysis was performed by using the Partial Least Square approach. The results showed that technology competencies have a positive relation to TPACK; likewise, the teachers’ attitudes in technology integration were able to strengthen the positive relation between technology competency and science teacher’s TPACK. Therefore, teacher's attitude is an important factor should be concerned in improving teacher's TPACK.